Proposals on Kaplan–Meier plots in medical research and a survey of stakeholder views: KMunicate. Issue 9 (30th September 2019) - Morris, Tim P; Jarvis, Christopher I; Cragg, William; Phillips, Patrick P J; Choodari-Oskooei, Babak; Sydes, Matthew R
Abstract : Objectives: To examine reactions to the proposed improvements to standard Kaplan–Meier plots, the standard way to present time-to-event data, and to understand which (if any) facilitated better depiction of (1) the state of patients over time, and (2) uncertainty over time in the estimates of survival. Design: A survey of stakeholders' opinions on the proposals. Setting: A web-based survey, open to international participation, for those with an interest in visualisation of time-to-event data. Participants: 1174 people participated in the survey over a 6-week period. Participation was global (although primarily Europe and North America) and represented a wide range of researchers (primarily statisticians and clinicians). Main outcome measures: Two outcome measures were of principal importance: (1) participants' opinions of each proposal compared with a 'standard' Kaplan–Meier plot; and (2) participants' overall ranking of the proposals (including the standard). Results: Most proposals were more popular than the standard Kaplan–Meier plot. The most popular proposals in the two categories, respectively, were an extended table beneath the plot depicting the numbers at risk, censored and having experienced an event at periodic timepoints, and CIs around each Kaplan–Meier curve. Conclusions: This study produced a high response number, reflecting the importance of graphics for time-to-event data. Those producing and publishing Kaplan–Meier plots—both authors and journals—should, as a starting point, consider using the combination of the two favoured proposals.